Diterpene Alkaloids from the Roots of Aconitum moldavicum and Assessment of Nav 1.2 Sodium Channel Activity of Aconitum Alkaloids - Borcsa, Botond; Fodor, László; Csupor, Dezső; Forgo, Peter; Molnár, Attila, V.; Hohmann, Judit (Planta Medica, 2014)
A new aconitane alkaloid, 1-O-demethylswatinine (1), was isolated from the root of Aconitum moldavicum together with the known compounds cammaconine (2), columbianine (3), swatinine (4), gigactonine (5), delcosine (6), lycoctonine (7), and ajacine (8). The structures were established by means of HRESIMS, 1D and 2D NMR spectroscopy, including 1H-1H COSY, NOESY, HSQC, and HMBC experiments, resulting in complete 1H-NMR chemical shift assignments for 1–4. The effects of the isolated compounds 4–8, together with eighteen other Aconitum diterpene and norditerpene alkaloids with different skeletal types and substitution patterns, were studied on Nav 1.2 channels by the whole-cell patch clamp technique, using the QPatch-16 automated patch clamp system. Pyroaconitine, ajacine, septentriodine, and delectinine demonstrated significant Nav 1.2 channel inhibition (57–42 %) at 10 µM concentration; several other compounds (acovulparine, acotoxicine, hetisinone, 14-benzoylaconine-8-O-palmitate, aconitine, and lycoctonine) exerted moderate inhibitory activity (30–22 %), while the rest of the tested alkaloids were considered to be inactive. On the basis of these results and by exhaustive comparison of data of previously published computerized QSAR studies on diterpene alkaloids, certain conclusions on the structure-activity relationships of Aconitum alkaloids concerning Nav 1.2 channel inhibitory activity are proposed.
Keywords: Aconitum moldavicum; Ranunculaceae; aconitine; norditerpene alkaloids; Nav 1.2 sodium channel inhibitory activity